2017
DOI: 10.3892/or.2017.5637
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces apoptotic cell death and protective autophagy in human gastric cancer cells

Abstract: Abstract. Curcumin possesses an anticancer effect against a wide assortment of tumors with selective cytotoxicity for tumor cells. However, the mechanism involved in the curcumin-induced anticancer effect remain unclear. In the present study, we investigated the efficacy of curcumin against human gastric cancer cell growth and the molecular mechanism involved. Our results demonstrated that curcumin inhibited the viabilities of gastric cancer cell lines BGC-823, SGC-7901 and MKN-28 in both a time-and dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…On the other hand, from the pathophysiological view of autophagy, which is generally regarded as a cellular adaptation mechanism to counteract cellular stress, for example in chemotherapy, that would trigger pro-survival signals escaping from apoptosis or cell death [ 34 , 35 ], the 5-Fu-triggered autophagy activation in our experiments may be a survival response of the colon cancer cells to the cytotoxic stimulus of 5-Fu. In addition to 5-Fu, curcumin has also been believed to be an autophagy regulator associated with its anti-cancer activity, for instance as an autophagy inducer in human gastric cancer cells [ 36 ], human melanoma cells [ 37 ], osteosarcoma MG63 cells [ 38 ] and HCT116 colon cancer cell line [ 39 ], and as a blocker in malignant mesothelioma cells [ 40 ]. The molecular changes underlying curcumin-mediated autophagic responses were also documented for cutaneous T-cell lymphoma to be relevant to the degradation of beclin-1, which is a component of class III phosphatidylinositol 3-kinase (IIIPI3K) and has an up-regulating effect on autophagosome [ 41 ], and thereby the accumulation of microtubule-associated protein-1 light chain 3 (LC3I), which promotes the death of the cancer cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, from the pathophysiological view of autophagy, which is generally regarded as a cellular adaptation mechanism to counteract cellular stress, for example in chemotherapy, that would trigger pro-survival signals escaping from apoptosis or cell death [ 34 , 35 ], the 5-Fu-triggered autophagy activation in our experiments may be a survival response of the colon cancer cells to the cytotoxic stimulus of 5-Fu. In addition to 5-Fu, curcumin has also been believed to be an autophagy regulator associated with its anti-cancer activity, for instance as an autophagy inducer in human gastric cancer cells [ 36 ], human melanoma cells [ 37 ], osteosarcoma MG63 cells [ 38 ] and HCT116 colon cancer cell line [ 39 ], and as a blocker in malignant mesothelioma cells [ 40 ]. The molecular changes underlying curcumin-mediated autophagic responses were also documented for cutaneous T-cell lymphoma to be relevant to the degradation of beclin-1, which is a component of class III phosphatidylinositol 3-kinase (IIIPI3K) and has an up-regulating effect on autophagosome [ 41 ], and thereby the accumulation of microtubule-associated protein-1 light chain 3 (LC3I), which promotes the death of the cancer cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, its glutathione S-transferase (GST) inhibition can lead to impaired detoxification and potential toxic drug−drug contraindications [186] or the human ether-a-go-go-related gene (hERG) channel inhibition which may lead to cardiotoxicity [187,188]. Second, high doses of curcumin have been reported to be toxic for cells inducing apoptosis [189]. In some studies of therapeutic utility, it has been shown as cytotoxic against a number of important cancer cell lines as mentioned before or even cytotoxic against normal human lymphocytes [190] and noncancerous cell lines [191].…”
Section: Curcumin Toxicitymentioning
confidence: 99%
“…Our study was coincident with the study of curcumin on bronchial epithelial cells of rats (Peng et al., 2017). However, there are inconsistent reports that curcumin has the potential to inhibit TOR signalling in human bladder cancer cells (Tian et al., 2017), human gastric cancer cells (Li et al., 2017), mouse prostate cancer cells (Narayanan, Nargi, Randolph, & Narayanan, 2009) and mouse cardiomyocytes (Yang, Xu, Li, & Jiang, 2013). The incongruous results of these studies illustrate that curcumin might promote TOR expression in normal cells, but inhibit its expression in pathological cells, which warrants further verification.…”
Section: Discussionmentioning
confidence: 99%